Región, Estado y nación en la sierra de Huánuco, siglo XIX Los conflictos entre Llata y La Unión por la hegemonía política en los Andes del Marañón - Espinoza Claudio, Cesar (2007)
This report aims at systematising the actions deployed by the national republican state over a region when trying to centralise and articulate its general and institutional policies while facing the emergence of a new regional elite settled in two Andean micro valleys of tributary rivers of Marañon: Llata and Aguamiro. Since 1845 the state intensifies the centralisation of its bureaucratic apparatus and its presence in the borders of Huamalies. The political hegemony of Llata will be challenged by other towns lead by Aguamiro and Huallanca that split the provincial unity of Huamalies and foster the creation of the province of Dos de Mayo. In short, we examine a set of variables that include geography, administration of justice, politics and regional identity in order to reconstruct and reflect on the links between State and Nation in the 19th. century.